Solar Power Shades for Dura Stadium - Alfaqyat, Rua; Abu Salameh, Safaa (جامعة بوليتكنك فلسطين - طاقة, 2021)
Using of renewable energy systems, especially solar energy, is one of the solutions for the production of sustainable and environmentally friendly electric power, this project aims at build a solar power system for Dura stadium and take advantage of the solar cells of this system as umbrellas for the seats of the masses, and after studying the consumption of the stadium where we took the consumption rate from 2013 to 2020 and this consumption amounts to 60,424 kwh/year , We noticed that consumption is not enough to cover the entire area of the stadium of 1118 m2 and so we relied on this area to build a system with a capacity of 152 kwp, and since there will be a surplus, there will be a contract between the municipality and the electricity company, and we are here in our turn to find out the fate of the surplus we had to know whether the area around the stadium receives this surplus or not? When studying the full load of the area around the stadium of approximately 4 MW, the maximum value of the surplus from renewable energy sources is 25% of the full load and thus receive a surplus of 1m, and after the establishment of the final design of the project we calculated quantities where the cost of the project is 558699 ILS.
CD, no of pages 109, طاقة 6/2021
Keywords: Solar Power Shades